PWE-213 Comparison of colonoscopy quality indicators between surgeons, physicians and nurse endoscopists in the NHS bowel cancer screening programme: analysis of the national database. (28th May 2012) - Lee, T J W; Nickerson, C; Rees, C J; Patnick, J; Rutter, M D; ,
Abstract : Introduction: Screening colonoscopists in the NHS Bowel Cancer Screening Programme (BCSP) are predominantly surgeons, physicians or nurse endoscopists. There are a small number from other backgrounds such as general practice. All are required to be screening-accredited, attain the same standards prior to commencing colonoscopy in the programme (including performance of at least 1000 colonoscopies) and undergo the same performance audits. This study examines whether there are any differences in colonoscopy quality indicators (CQI) among colonoscopists from these different backgrounds. Methods: The following CQI were calculated for all colonoscopists in the BCSP based on all index screening colonoscopies performed between August 2006 and August 2009: adenoma detection rate (ADR), polyp detection rate (PDR), mean number of adenomas per patient (MAP), mean negative complete colonoscopy withdrawal time (nc-CWT), caecal intubation rate (CIR), rectal retroversion rate (RRR), polyp retrieval rate (PRR), percentage of patients with no, minimal or mild discomfort and percentage of procedures performed with no intravenous sedation. Colonoscopists were classified according their background. As only one colonoscopist was from a general practice background, this group was not included from subsequent analyses. ANOVA was used to compare the mean values for each of the CQI for each speciality. Results: Of 148 colonoscopists, 114 were physicians, 24 were surgeons and 10 were nurse endoscopists. In the study period, 36 460 colonoscopies were performed. The mean ADR for surgeons, physicians and nurse endoscopists were 46.7%, 46.6% and 44.2% respectively. The mean CIR rates were 95.3%, 95.3% and 94.7% respectively. These values were not significantly different (p=0.570, p=0.839). Similarly, no significant differences were seen in comparison of any of the other CQI or performance indicators (PDR, MAP, nc-CWT, RRR, PRR or patient comfort). The proportion of procedures performed without sedation by surgeons, physicians and nurse endoscopists were 10.4%, 13.8% and 27.5% respectively (p=0.002). Conclusion: This study demonstrates that standards of colonoscopy as assessed by eight colonoscopy quality indicators and measures of performance are similar for surgeons, physicians and nurse endoscopists. The difference in percentage of procedures performed without sedation may reflect differing attitudes to sedation and warrants further investigation. These data support the accreditation process for screening colonoscopists by demonstrating that all accredited colonoscopists perform to a high standard irrespective of speciality. Competing interests: None declared.